Development of Basic Volleyball Learning Media Based on Web Learning Materials Towards KKNI at Universitas Negeri Medan - Indrakasih Indrakasih; Bangun Setia; Onyas Widianingsih; Deni Rahman (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This research was funded by BOPTN funding. This research is focused on the Development of Basic Volleyball Learning Media Based on Web Learning Materials Towards KKNI at Fik Medan State University. This research is a research and development. After researching the results of volleyball basic technical skills based on learning groups, namely the posttest experimental group (new model, web learning) and the pretest experimental group (old model), it is found that the results of basic ball technical skills volleyball in the posttest experimental group ie the lowest score of 80 and the highest score of 90. Whereas in the pretest experimental group, the results of volleyball basic technique ability obtained the lowest score of 70 and the highest score of  90. The average score and standard deviation in the posttest experimental group were 82.00 and 4.14, while in the pretest experimental group amounted to 78.00 and 8.62. When viewed from the distribution of questionnaires to see new model learning is more effective than old model learning. The average effectiveness of the old model learning outcomes indicator is 86.57% and the learning model is new or uses web learning 98.77%. So it can be concluded that learning new models is more effective than learning models.